Kebijakan Hukum Pidana (Penal Policy) Terhadap Rumusan Tindak Pidana Terhadap Sifat Tidak Memihak Hakim - Rizka Fakhry Alfiananda (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
Indonesian tendency to control the behavior of their people through the penal policy returns seen in the formulation of crime against the independence of judiciary. The formulation of the crime intended to control people's behavior in relation to the judicial process in order not to affect the independence of the judiciary. The formulation of crime are urgently given considered by degradation of the current authority, dignity, and honor of the judiciary due to the intervention of the parties concerned over a judicial process. If the intervention is allowed, then the purpose of the judiciary to uphold the law and justice will not be achieved. However, the formulation of the crime was rejected by many party due to the vagueness of formulation of a crime can be used as an instrument for acting arbitratrily by certain elements.